Aikido: via para ascese marcial - Santos, Fernanda Damasceno [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Aikido is a Japanese martial art developed in the 20th century by Morihei Ueshiba. This self defense art, as it is known, is trained around the world as a noncompetitive practice. This work aimed to investigate and circumscribe the history of this martial art presenting features of its singularity. Akido´s Cultural History was used as a theoretical approach to build the historical background. The work was divided in five chapters as respectively named and described: Japan´s historical contextualization - it seeks to show the changing processes that happened in Japan which were arising from the insertion of other cultures, and how that insertion led the country to modernize itself and turn into a great world power. The ancient art: Aiki Jujutsu Daitoryu - talks about this samurai martial art which ensured the Aikido to obtain as the source technique the aiki, and the Xintoist practice. The history of a master: Morihei Ueshiba - presents some defining facts and moments from the master Ueshiba´s history, which points both to the changes occurred in the country, and to the ones that led the master to justify and broadcast the martial art. Aikido: The Budo art - portraits the Aikido´s meaning and the way that it was built to present the Aikido as a Budo art. And to finalize, Martial asceticism - seeks to make the dialogue between the cultures, from the meaning of this chapter title words (martial asceticism), as well as to point facts from the contemporaneity which provoke reflections upon the present practice

O Aikido é uma arte marcial japonesa desenvolvida no século XX por Morihei Ueshiba. Essa arte de defesa-pessoal, assim como é conhecida, é treinada pelo mundo todo como prática não competitiva. Este trabalho objetivou investigar e circunscrever a história desta arte marcial apresentando as características de sua singularidade. Foi utilizada a História Cultural como abordagem teórica para construir o acervo histórico do Aikido. O trabalho foi dividido em cinco capítulos assim nomeados e descritos respectivamente: Contextualização histórica do Japão - procura apresentar os processos de mudanças ocorridas no Japão que foram decorrentes da inserção de outras culturas, e como esta inserção levou o país a se modernizar e se tornar uma grande potência mundial. A arte milenar: Aiki Jujutsu Daitoryu - discorre sobre essa arte marcial samurai que garantiu ao Aikido obter como fonte de técnica o aiki, e a prática Xintoísta. A história de um mestre: Morihei Ueshiba - apresenta alguns fatos e momentos marcantes da história do mestre Ueshiba, que apontam tanto para as mudanças ocorridas no país, como também as que levaram o mestre a fundamentar e difundir a arte marcial. Aikido: A arte do Budo - retrata o signicado do Aikido e o caminho que foi construído para apresentar o Aikido como arte do Budo. E para fechar, Ascese Marcial - procura fazer o diálogo entre as culturas, partindo do significado das palavras contidas no título deste capítulo (ascese marcial), como também apontar fatos da contemporaneidade que provocam reflexões sobre a prática presente
Keywords: Defesa pessoal; Aikido; Luta corporal oriental; Espiritualidade; Ascetismo; Artes marciais; Aikido; Self-defense; Hand-to-hand fighting, Oriental; Spirituality; Asceticism; Martial arts